Keynote address: Innovation: Key to future agri-food production - Dijkhuizen, Aalt (New Zealand Science Review, 2010)
​World food security must be attained, despite emerging issues and major challenges mentioned in this paper. But this will depend on major investment in technology and innovations. Highly productive agriculture is needed; particularly indispensible are productivity increases per hectare and per animal. Above all, worldwide partnering is essential if we are to address the challenges of today.